math,algebra
posted by jasmine20 .
what error am i doing here? can someone explain to me.
The equation: 2(x – 2) = x + 3
First step in solving:
Respond to this Question
Similar Questions

Algebra II please help!
I just cannot seem to be able to grasp the concept of solving polynomial inequalities. Can someone please explain, step by step, how to solve them? 
algebra 1
ELEMENTARY ALGEBRA #3 Page 23 Chapter 3 Lesson 3.02 Solving Multistep Equations Reading Assignment: Study pages 126 – 129 Written Assignment: There are five steps to solve MultiStep equations, Match them in their proper order. … 
algebra
When solving a rational equation what is the first step we must always take? 
algebra
Can someone show me the step to solving this equation because I am just not getting it. My teacher is confusing me, so I need someone else to explain it in a different uncomplicated way. y1/x+3 = 3/4.Thanks so much you guys for the … 
algebra II
Select the best possible first step to solving the system by first eliminating the y variable. x + 8y = –4 2x – 4y = –13 Multiply the first equation by 2. Multiply the second equation by 2. Multiply the first equation by –2. … 
ALGEBRA HELP
When solving the equation, what property was used to go from step 3 to step 4? 
math
An equation and the steps to solve it are shown below: 3x − one over two (8x − 2) = 4 Step 1: 3x − 4x + 1 = 4 Step 2: x + 1 = 4 Step 3: x + 1 − 1 = 4 − 1 Step 4: x = 3 Which step was the error made and … 
math
An equation and the steps to solve it are shown below: 3x − one over two (8x − 2) = 4 Step 1: 3x − 4x + 1 = 4 Step 2: x + 1 = 4 Step 3: x + 1 − 1 = 4 − 1 Step 4: x = 3 Which step was the error made and … 
Math
I need help solving the problem not the answer. (Multiple Choice) The steps below show the incomplete solution to find the value of x for the equation 7x + 8 − 3x = −6 + 10: Step 1: 7x + 8 − 3x = −6 + 10 Step 2: 7x + 8 − … 
Math Help
An equation is shown below: 4(2x  5) + 15 = 11 Write the steps you will use to solve the equation and explain each step. Can someone please explain step by step this equation?